1986
DOI: 10.1128/mcb.6.6.2253
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional control of human gamma interferon gene expression in transfected mouse fibroblasts.

Abstract: Human gamma interferon genomic DNA was introduced into NIH 3T3 fibroblasts by calcium phosphate precipitation and was not expressed in these cells at the cytoplasmic mRNA or protein level. Treatment of the transfected cells with cycloheximide (1 ,ug/ml) induced the accumulation of cytoplasmic gamma interferon mRNA and biologically active human gamma interferon. Analysis of the nuclear enriched RNA from untreated cells indicated that human gamma interferon mRNA was present, suggesting that cycloheximide may act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…The necessity for such precise regulation is consistent with the finding that inappropriate expression of these and other mRNAs and their protein products can interfere with cell replication and differentiation (1,7,12,30,31,39,47). mRNAs whose decay rates seem to be regulated include those expressed from proto-oncogenes (13,15,20,35,41,72); genes related to cell division, including the histones (reviewed in reference 36); acute-phase response and inflammatory response genes (3,19); interferon genes (80); heat shock protein genes (65,71); and developmentally regulated gehes (16,62,73).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The necessity for such precise regulation is consistent with the finding that inappropriate expression of these and other mRNAs and their protein products can interfere with cell replication and differentiation (1,7,12,30,31,39,47). mRNAs whose decay rates seem to be regulated include those expressed from proto-oncogenes (13,15,20,35,41,72); genes related to cell division, including the histones (reviewed in reference 36); acute-phase response and inflammatory response genes (3,19); interferon genes (80); heat shock protein genes (65,71); and developmentally regulated gehes (16,62,73).…”
mentioning
confidence: 56%
“…The activity becomes apparent following estrogen withdrawal. (ii) Translation inhibitors induce the accumulation of various mRNAs, a phenomenon frequently referred to as superinduction (3,13,20,35,41,(71)(72)(73)80). Although the mechanism of superinduction is incompletely understood, our in vitro experiments suggest that, in some instances, it might involve inactivation of destabilizer activities.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, it has become apparent that many genes are regulated at the posttranscriptional level (8,24,36). One notable instance involves the immunoglobulin heavy-chain gene.…”
mentioning
confidence: 99%
“…These studies indicate that increased levels of immunoglobulin gene expression in plasma cells are dependent upon posttranscriptional mechanisms. Furthermore, the induction of human beta and gamma interferon expression (22,36), the developmental regulation of the psp gene in the mouse parotid gland (33), and the tissue-specific expression of glyceraldehyde 3-phosphate dehydrogenase in rat tissue (21) all appear to be partially controlled by posttranscriptional events.The cis-acting sequences that act posttranscriptionally to regulate gene expression are not known for many of these cases. However, an AT-rich sequence has recently been identified that causes selective mRNA degradation when introduced into the 3' untranslated region of the ,B-globin gene, which normally produces a stable mRNA (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation